Sharia-based Financial Intelligence for Children and Adolescents - Nurishlah, Laesti; Gustaman; Hermansyah, Yus; Nurfitria, Desi (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
Sharia-based financial intelligence for children and adolescents includes aspects of Islamic values education, character development, preparation for the economic future, equitable financial inclusion, financial risk management, and continuing education. This study aims to analyze Sharia-based financial intelligence for children and adolescents. The research method used is library research with a qualitative approach. The results of the study show that the potential for intelligence of children and adolescents in understanding sharia-based finance is very large, considering their ability to learn and absorb information from an early age. Children and adolescents tend to have the ability to grasp new concepts and information quickly. This allows them to understand the basic principles of Sharia economics such as the prohibition of usury, the concept of profit-sharing-based financing, and the importance of social responsibility in financial management. Children and adolescents can develop awareness about the importance of sharing wealth with others through zakat, infaq, and sadaqah. This not only teaches them about social responsibility but also strengthens their bonds with the community and society at large. By making optimal use of this potential, children and adolescents can become a Shariah-based financially educated generation, able to make wise and sustainable financial decisions by Islamic values.